Germline nuclear transfer in mice may rescue poor embryo development associated with advanced maternal age and early embryo arrest. Issue 7 (2nd July 2020) - Tang, M; Popovic, M; Stamatiadis, P; Van der Jeught, M; Van Coster, R; Deforce, D; De Sutter, P; Coucke, P; Menten, B; Stoop, D; Boel, A; Heindryckx, B
Abstract: STUDY QUESTION: Can pronuclear transfer (PNT) or maternal spindle transfer (ST) be applied to overcome poor embryo development associated with advanced maternal age or early embryo arrest in a mouse model? SUMMARY ANSWER: Both PNT and ST may have the potential to restore embryonic developmental potential in a mouse model of reproductive ageing and embryonic developmental arrest. WHAT IS KNOWN ALREADY: Germline nuclear transfer (NT) techniques, such as PNT and ST, are currently being applied in humans to prevent the transmission of mitochondrial diseases. Yet, there is also growing interest in the translational use of NT for treating infertility and improving IVF outcomes. Nevertheless, direct scientific evidence to support such applications is currently lacking. Moreover, it remains unclear which infertility indications may benefit from these novel assisted reproductive technologies. STUDY DESIGN, SIZE, DURATION: We applied two mouse models to investigate the potential of germline NT for overcoming infertility. Firstly, we used a model of female reproductive ageing (B6D2F1 mice, n  = 155), with ages ranging from 6 to 8 weeks (young), 56 (aged) to 70 weeks (very-aged), corresponding to a maternal age of <30, ∼36 and ∼45 years in humans, respectively. Secondly, we used NZB/OlaHsd female mice (7–14 weeks, n  = 107), as a model of early embryo arrest. This mouse strain exhibits a high degree of two-cell block. Metaphase II (MII) oocytes and zygotes were retrieved following superovulation. PARTICIPANTS/MATERIALS, SETTING, METHODS: Ovarian reserve was assessed by histological analysis in the reproductive-aged mice. Mitochondrial membrane potential (△Ψ m ) was measured by JC-1 staining in MII oocytes, while spindle-chromosomal morphology was examined by confocal microscopy. Reciprocal ST and PNT were performed by transferring the meiotic spindle or pronuclei (PN) from unfertilised or fertilised oocytes (after ICSI) to enucleated oocytes or zygotes between aged or very-aged and young mice. Similarly, NT was also conducted between NZB/OlaHsd (embryo arrest) and B6D2F1 (non-arrest control) mice. Finally, the effect of cytoplasmic transfer (CT) was examined by injecting a small volume (∼5%) of cytoplasm from the oocytes/zygotes of young (B6D2F1) mice to the oocytes/zygotes of aged or very-aged mice or embryo-arrest mice. Overall, embryonic developmental rates of the reconstituted PNT ( n  = 572), ST ( n  = 633) and CT ( n  = 336) embryos were assessed to evaluate the efficiency of these techniques. Finally, chromosomal profiles of individual NT-generated blastocysts were evaluated using next generation sequencing. MAIN RESULTS AND THE ROLE OF CHANCE: Compared to young mice, the ovarian reserve in aged and very-aged mice was severely diminished, reflected by a lower number of ovarian follicles and a reduced number of ovulated oocytes ( P  <   0.001). Furthermore, we reveal that the average △Ψ m in both aged and very-aged mouse oocytes was significantly reduced compared to young mouse oocytes ( P  <   0.001). In contrast, the average △Ψ m in ST-reconstructed oocytes (very-aged spindle and young cytoplast) was improved in comparison to very-aged mouse oocytes ( P  <   0.001). In addition, MII oocytes from aged and very-aged mice exhibited a higher rate of abnormalities in spindle assembly ( P  <   0.05), and significantly lower fertilisation (60.7% and 45.3%) and blastocyst formation rates (51.4% and 38.5%) following ICSI compared to young mouse oocytes (89.7% and 87.3%) ( P  <   0.001). Remarkably, PNT from zygotes obtained from aged or very-aged mice to young counterparts significantly improved blastocyst formation rates (74.6% and 69.2%, respectively) ( P  <   0.05). Similarly, both fertilisation and blastocyst rates were significantly increased after ST between aged and young mice followed by ICSI ( P  <   0.05). However, we observed no improvement in embryo development rates when performing ST from very-aged to young mouse oocytes following ICSI ( P  >   0.05). In the second series of experiments, we primarily confirmed that the majority (61.8%) of in vivo zygotes obtained from NZB/OlaHsd mice displayed two-cell block during in vitro culture, coinciding with a significantly reduced blastocyst formation rate compared to the B6D2F1 mice (13.5% vs. 90.7%; P  <   0.001). Notably, following the transfer of PN from the embryo-arrest (NZB/OlaHsd) zygotes to enucleated non-arrest (B6D2F1) counterparts, most reconstructed zygotes developed beyond the two-cell stage, leading to a significantly increased blastocyst formation rate (89.7%) ( P  <   0.001). Similar findings were obtained after implementing ST between NZB/OlaHsd and B6D2F1 mice, followed by ICSI. Conversely, the use of CT did not improve embryo development in reproductive-age mice nor in the embryo-arrest mouse model ( P  >   0.05). Surprisingly, chromosomal analysis revealed that euploidy rates in PNT and ST blastocysts generated following the transfer of very-aged PN to young cytoplasts and very-aged spindles to young cytoplasts were comparable to ICSI controls (with young mouse oocytes). A high euploidy rate was also observed in the blastocysts obtained from either PNT or ST between young mice. Conversely, the transfer of young PN and young spindles into very-aged cytoplasts led to a higher rate of chromosomal abnormalities in both PNT and ST blastocysts. LARGE SCALE DATA: N/A LIMITATIONS, REASONS FOR CAUTION: The limited number of blastocysts analysed warrants careful interpretation. Furthermore, our observations should be cautiously extrapolated to humans given the inherent differences between mice and women in regards to various biological processes, including centrosome inheritance. The findings suggest that ST or PNT procedures may be able to avoid aneuploidies generated during embryo development, but they are not likely to correct aneuploidies already present in some aged MII oocytes. WIDER IMPLICATIONS OF THE FINDINGS: To our knowledge, this is the first study to evaluate the potential of PNT and ST in the context of advanced maternal age and embryonic developmental arrest in a mouse model. Our data suggest that PNT, and to a lesser extent ST, may represent a novel reproductive strategy to restore embryo development for these indications. STUDY FUNDING/COMPETING INTEREST(S): M.T. is supported by grants from the China Scholarship Council (CSC) (Grant no. 201506160059) and the Special Research Fund from Ghent University (Bijzonder Onderzoeksfonds, BOF) (Grant no. 01SC2916 and no. 01SC9518). This research is also supported by the FWO-Vlaanderen (Flemish fund for scientific research, Grant no. G051017N, G051516N and G1507816N). The authors declare no competing interests. TRIAL REGISTRATION NUMBER: N/A